2019
DOI: 10.1371/journal.pone.0211622
|View full text |Cite
|
Sign up to set email alerts
|

Trend and projection of mortality rate due to non-communicable diseases in Iran: A modeling study

Abstract: Background Following the epidemiologic and demographic transition, non-communicable disease mortality is the leading cause of death in Iran. Projecting mortality trend can provide valuable tools for policy makers and planners. In this article, we have estimated the trend of non-communicable disease mortality during 2001–2015 and have projected it until 2030 at national and subnational levels in Iran. Methods The data employed was gathered from the Iranian death registra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…Also, obesity and diabetes have big impacts on fatty liver and ultimately liver cancer [ 28 , 29 ]. In a study by the same researchers who carried out the present study, it was shown that obesity and diabetes in Iran are on the rise and this trend will continue in the future which can be one of the factors contributing to the increased number of in liver cancer among Iranian population [ 30 ]. Another reason is the lack of vaccination among the age group of 30–70 year olds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, obesity and diabetes have big impacts on fatty liver and ultimately liver cancer [ 28 , 29 ]. In a study by the same researchers who carried out the present study, it was shown that obesity and diabetes in Iran are on the rise and this trend will continue in the future which can be one of the factors contributing to the increased number of in liver cancer among Iranian population [ 30 ]. Another reason is the lack of vaccination among the age group of 30–70 year olds.…”
Section: Discussionmentioning
confidence: 99%
“…Gallbladder cancer is associated with obesity [ 31 ]. Given the increased obesity prevalence in both sexes [ 30 ], it can be considered as one of the factors in the increasing trend of gallbladder cancer mortality, especially among females. Since the prevalence of obesity in females is higher than in males, there may be another unknown risk factor in the incidence and mortality of this cancer that should be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the country has a drug shortage for some of these medicines and those for chronic non-communicable diseases (NCDs) and older individuals. Iran has high rates of chronic non-communicable diseases such as cancer, diabetes, hypertension, etc 17,18 , which has a high financial burden. Even before the COVID-19 outbreak, Iran has difficulties for providing medications for these patients 19 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Is should be noted that the Iran's population is aging (Figure 2 and supplementary figure 1) 49 . Also, the burden of chronic and NCDs are increasing in Iran 17,18 . Due to the high economic burden of medications and healthcare services in older individuals and NCDs…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…High burden of NCDs and annual loss of thousands people due to non-communicable diseases as high political commitment to tackle NCDs in Iran [9]. Accordingly, Iran has established National Non-Communicable Diseases Committee (INCDC) through multi-sectoral mechanism and partnership of all sectors in the Ministry of Health and Medical Education and other related sectors and ministries, organizations, NGOs, and communities [10].…”
mentioning
confidence: 99%